(untitled) (Research, Society and Development, 2020)
This paper aims to analyze occurrences of suicide in Brazil between 1996 and 2016 and related epidemiological variables. This is a descriptive retrospective study of a historical series based on secondary data obtained in June 2018 from the Mortality Information System (SIM) of the Department of Informatics of the Unified Health System (DATASUS). The suicide mortality rate increased from 4.29 in 1996 to 5.55 in 2016. The South Region had the highest mortality rate in all years, followed by the Midwest Region. A total of 145,030 (79.04%) deaths from suicide of men and 38,419 (20.94%) of women were recorded; 42,040 suicides by people aged between 20 and 29 years, 39,096 between 30 and 39 years, 33,999 between 40 and 49 years; 92,007 by white people, 59,373 brown, 9,011 black; 89,262 were single, 57,848 married; 103,617 (56.47%) occurred in households; 36,689 had between 4 and 7 years of schooling, 26,822 with 8 to 11 years of schooling, 24,859 with 1 to 3 years of schooling, 11,673 with 12 or more years of schooling and 10,279 with no schooling; hanging is the most used method in suicide occurrences. The Brazilian government needs to implement a surveillance program for suicidal behavior.